Association of outdoor air pollution with the prevalence of asthma in children of Latin America and the Caribbean: A systematic review and meta-analysis. (2nd November 2018) - Orellano, Pablo; Quaranta, Nancy; Reynoso, Julieta; Balbi, Brenda; Vasquez, Julia
ABSTRACT: Objective : This study aimed to evaluate the association between asthma prevalence and outdoor air pollution in children in Latin America and the Caribbean. Data Sources : We searched studies in global and regional databases: PubMed, Scopus, LILACS and SciELO. Study Selection : Articles following a cross-sectional design, studying children from 0 to 18 years old, and comparing the prevalence of asthma in two or more areas of LAC countries with different air pollution levels were included. The exclusion criteria comprised air pollution not related to human activities. Results : Database searches retrieved 384 records, while 20 studies were retained for qualitative and 16 for quantitative analysis, representing 48 442 children. We found a positive association, i.e. a higher prevalence of asthma in children living in a polluted environment, with pooled odds ratio (OR) of 1.34 (95% CI: 1.17–1.54). Heterogeneity between studies was moderate (I 2 : 68.39%), while the risk of bias was intermediate or high in 14 studies. In all the subgroup and sensitivity analyses, the pooled ORs were significant and higher than those found in the general analysis Conclusions : Our results showed that living in a polluted environment is significantly associated with children having asthma in LAC. Limitations of this study include the low number of studies performed in LAC countries, differences in methodologies and the risk of bias in individual studies.